Philosophical Excursus I. Seriousness, play, and fame (on Rorty’s Derrida) - Kwiek, Marek (My University, 1996)
Reading numerous readings of Jacques Derrida made by Richard Rorty during the period of the last twenty years or so, one can get the impression that Rorty admires French deconstructionist without reservations, presenting him as an example of a new way of practising philosophy - a way which is private, idiosyncratic and publicly uncommitted, which is original, but publicly useless, which, finally, leads to individual autonomy. A way leading to self-creation, getting out of the influence and power of one’s precursors by way of a para-Oedipal struggle of a son with a father (which is the motive of "strong poets" from Harold Bloom’s The Anxiety of Influence). Derrida in Rorty would be supposed to break with Heidegger in the way Heidegger tried to overcome Nietzsche, and Nietzsche struggled with Plato. And just like Nietzsche wished to be a new figure of a philosopher who "philosophizes with a hammer", but in Heidegger’s reading turned out to be merely "the last metaphysician" and "inverted Platonic", similarly Heidegger in the eyes of Derrida is not - despite the former’s assurance and unshakeable self-confidence - the first post-metaphysical thinker, but precisely the "last metaphysician", the last figure from the "ontotheological tradition" being destroyed or from the tradition of the "metaphysics of presence". Derrida overcomes Heidegger, Rorty reminds us, when he is trying to be the first post-metaphysical philosopher e.g. when he says that "there will be no unique name, even if it were the name of Being" ("Differance"), about which, incidentally, he already spoke as a broader project in a volume of interviews entitled Positions, telling his interviewer that he is attempting to locate in Heidegger’s texts "the signs of belonging to metaphysics". But philosophical search for fame - and hence immortality - leads to an infinite number of recontextualizations and redescriptions, to new readings fighting with old ones, and the characters of philosophical stories being told are philosophers who are closer and closer to us. And just like Jacques Derrida was not willing to leave Heidegger in peace until he overcame him (although he is still struggling with him), putting himself in a new light, similarly Richard Rorty relentlessly bites in his own way Derrida’s philosophizing.
Keywords: Richard Rorty; Jacques Derrida; American pragmatism; new pragmatism; deconstruction; deconstructivism; French postmodernism; Nietzscheanism; Heideggerianism; fame; strong reading; liberal ironist; Contingency, Irony, and Solidarity; the public/private split; solidarity and self-creation; philosophy and literature; responsibility; social engagement; public intellectual; postwar French philosophy; Rorty and Continental Philosophy; strong misreading; anxiety of influence; strong poet; Harold Bloom; the Kant-Plato canon; Philosophy and the Mirror of Nature; Philosophy as a Kind of Writing; Consequences of Pragmatism; From Ironist Theory to Private Allusions: Derrida; The Postcard; Deconstruction and Circumvention; Specters of Marx; The Philosophical Discourse of Modernity; difference